Non Noble Metal Catalyst for Oxygen Reduction Reaction and Its Characterization by Simulated Fuel Cell Test. Issue 15 (1st January 2018) - Zhan, Yunfeng; Xie, Fangyan; Zhang, Hao; Lin, Zhipeng; Huang, Jilin; Zhang, Weihong; Sun, Xueliang; Zhang, Yueli; Chen, Jian; Meng, Hui
Abstract : In this work nitrogen doped multi-layer graphene and porous carbon are prepared by the pyrolysis of glycine as precursor. The morphology of the product is controlled by the catalyst used. The nitrogen doped multi-layer graphene exhibits a high onset potentialand four-electron pathway for oxygen reduction reaction (ORR) in alkaline solution as well as much enhanced stability compared with commercial Pt/C catalyst. In a simulated fuel cell test the nitrogen doped multi-layer graphene shows comparable performance with Pt/C catalyst in alkaline environment. The ORR activity of the as-prepared carbon material is found to be related with graphitization degree and graphitic-N.